2023
DOI: 10.4038/jas.v18i1.10100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Some Biochemical Characteristics of Seminal Plasma in Wild and Cultured Male Catfish (<em>Clarias gariepinus</em>), Burchell, 1822 Broodstock

Abstract: Purpose:In aquaculture, the most important aspect to consider is ensuring the development of valuable offspring by using high-quality gametes from fish broodstock. This research aims to compare the biochemical constituents of seminal plasma in both wild and cultured Clarias gariepinus broodstock.Research Method: Apparently healthy adult male Clarias gariepinus (n=9, 900±300g mean weight per fish type (wild or cultured), 49±8.5cm mean total length) were collected from fishermen on the Oshin River, Nigeria for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…In the present study, the weight, diameter and length of the testes was not significant between spawning and nonspawning periods. These, findings agree with those of Idahor et al (2014) and Yusuf et al (2015), but have slightly lower values in comparison to the study by Zakariah et al (2016), this could be due to the higher number of fish used in the current study. The testes and reproductive organs of C. gariepinus during spawning period as observed in this study were lobular and whitish as compared to during nonspawning season that appears smooth and pinkish (figure 1).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the weight, diameter and length of the testes was not significant between spawning and nonspawning periods. These, findings agree with those of Idahor et al (2014) and Yusuf et al (2015), but have slightly lower values in comparison to the study by Zakariah et al (2016), this could be due to the higher number of fish used in the current study. The testes and reproductive organs of C. gariepinus during spawning period as observed in this study were lobular and whitish as compared to during nonspawning season that appears smooth and pinkish (figure 1).…”
Section: Discussionsupporting
confidence: 92%
“…The age and body weight of brood stock has a significant influence on the sperm quality and may affect the success of storing sperm (Vuthiphandchai and Zohar, 2007;Azlina et al, 2011;Dominic and Abiodun, 2014). In this study, there was a significant (p˂ 0.05) positive correlation between body weight of fish and milt volume in spawning and nonspawning seasons which corresponded with a similar finding by Gjerde (1984) and Yusuf et al (2015); who has also reported a positive correlation between volume of milt and body size (weight and length) in Atlantic salmon (Salmosalar) and rainbow trout and the later on cultured African catfish which signifies that higher body weight fish tends to have an increased in the volume of milt than lower body weight fish, or probably due to physiological constraints (Stockley et al, 1996).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation